1984
DOI: 10.1099/0022-1317-65-8-1285
|View full text |Cite
|
Sign up to set email alerts
|

Hantaan Virus: Identification of Virion Proteins

Abstract: SUMMARYSDS-PAGE and immunoprecipitation analyses were carried out on the virion and cell-associated proteins of Hantaan virus, the causative agent of haemorrhagic fever with renal syndrome (HFRS). Purified virions have a density of 1.17 g/ml in sucrose, and contain four proteins with molecular weights of 45 000 (45K), 56K, 72K and 200K, confirming recent evidence that the virus is a member of the family Bunyaviridae. Detergent treatment of virions indicates that the 45K protein is the virus nucleoprotein. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…wt.) which may represent the virion-associated polymerase Schmaljohn & Dalrymple, 1984;Elliott et al, 1984). Examination of the kinetics of synthesis of Hantaan virus proteins within infected cells revealed that at a high multiplicity of infection, viral polypeptides could first be detected at 6 h post-infection, quantitatively increased up to 24 h, then remained constant up to 56 h (Schmaljohn & Dalrymple, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…wt.) which may represent the virion-associated polymerase Schmaljohn & Dalrymple, 1984;Elliott et al, 1984). Examination of the kinetics of synthesis of Hantaan virus proteins within infected cells revealed that at a high multiplicity of infection, viral polypeptides could first be detected at 6 h post-infection, quantitatively increased up to 24 h, then remained constant up to 56 h (Schmaljohn & Dalrymple, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The S RNA segment encodes the nucleocapsid protein (N) and the M RNA segment encodes a glycoprotein precursor that is cleaved into the envelope glycoproteins G1 and G2 (Schmaljohn et al, 1986(Schmaljohn et al, , 1987Yoo & Kang, 1987b;Giebel et al, 1989;Stohwasser et al, 1990;Parrington & Kang, t990;Arikawa et al, 1990). The L segment is believed to encode the RNA polymerase (Elliott et al, 1984). The G1 and G2 proteins of Hantaan virus have been demonstrated to have neutralizing epitopes (Yamanishi et al, 1984;Dantas et al, 1986;Arikawa et al, 1989;Schmaljohn et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Hantaviruses constitute a genus in the Bunyaviridae, a large family of viruses with more than 350 characterized members (6,22,24,32). In contrast to the arthropod-borne members of the other genera (Orthobunya-, Nairo-, Phlebo-, and Tospovirus), hantaviruses are rodent-borne (24).…”
mentioning
confidence: 99%